Who's responsible? Representatives' autonomy alters customers' emotion and repurchase intentions toward organizations. Issue 1 (25th January 2019) - Shank, Daniel B.; Robinson, Dawn T.
Abstract : Purpose: This paper aims to present and test a model of how the autonomy of an organization's representative alters the effects of customer experiences on customer emotions and repurchasing intentions toward the organization. Specifically, this paper offers a moderated mediation model whereby representative autonomy alters attributions of organizational responsibility, which moderate the effect of service experience on emotion and emotion mediates the effects of service experiences on repurchasing intentions. Design/methodology/approach: Study 1 is a laboratory experiment ( N = 115), where participants engaged in a multi-round product purchasing task through an online representative of a company. Study 2 is a vignette experiment ( N = 393), where participants responded to situations of purchasing either a car, furniture, haircut or vacation package from a representative of a company. In both studies, manipulated representative autonomy information was either low or high and manipulated customer experience was either positive or negative. Measures included responsibility, emotion toward the organization and repurchase intention. Findings: Structural equation models support the proposed model. In the presence of information about representative autonomy, the link between customer experience and repurchasing intent is amplified and mediated by emotion toward the organization. Research limitations/implications: Because of the experimental approach, the findings may not be generalizable, but the experimental method allows for a controlled test of the process, ordering and relationship among variables. Originality/value: Understanding how representatives' autonomy ultimately alters repurchasing and how this process involves responsibility attributions contributes to both practice and theory.